2012
DOI: 10.2106/jbjs.l.00142
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Navigated Versus Conventional Total Knee Arthroplasty

Abstract: Our data demonstrated no difference in clinical function or alignment and survivorship of the components between the knees that underwent computer-navigated total knee arthroplasty and those that underwent conventional total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
128
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 29 publications
10
128
3
4
Order By: Relevance
“…The results of this study confirm those that have shown no statistically significant difference in implant alignment between CATKR and JATKR [18][19][20], and as such produces further evidence that the routine use of navigation is not required to improve either implant positioning or functional outcome in patients with knee arthritis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of this study confirm those that have shown no statistically significant difference in implant alignment between CATKR and JATKR [18][19][20], and as such produces further evidence that the routine use of navigation is not required to improve either implant positioning or functional outcome in patients with knee arthritis.…”
Section: Discussionsupporting
confidence: 86%
“…Multiple studies have assessed the accuracy of computer assisted procedures over the traditional jig-assisted method in improving component alignment with varying results [17][18][19][20][21]. The results of this study confirm those that have shown no statistically significant difference in implant alignment between CATKR and JATKR [18][19][20], and as such produces further evidence that the routine use of navigation is not required to improve either implant positioning or functional outcome in patients with knee arthritis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A vascular lesions during tracker placement have been described as rare complication [17]. Previous 5-year results following computernavigated TKA have shown no improvement in function or clinical knee score measurements in comparison with conventional TKA [18,21,24,26,29,33]. However, long-term [25] came to the conclusion that the use of a navigation system with measured resection TKA can help optimise coronal stability and parallel component position.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 An unusual error in displaying the numerical measurements that was encountered in the middle of the surgery, following which how the error was rectified is presented in this study. It had also been tried to trace out the possible cause of error that could be attributed to the numerical mismatch which was encountered during the surgery to avoid future recurrence.…”
Section: Introductionmentioning
confidence: 91%